LEVERAGING LANGUAGE LEARNING STRATEGIES AND MOTIVATIONS TO DEVELOP INTERCULTURAL AWARENESS - Nur Alfiana Isnaini; Yazid Basthomi; Mirjam Anugerahwati (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
Incorporating intercultural competence in the classroom may be a demand these days. As a required skill, intercultural competence has attracted much attention in EFL learning. Therefore, this study aims to scrutinize the types of language learning strategies and students' motivation to learn English and how those strategies and types of motivation can elevate students' intercultural awareness. This study implements the development of intercultural sensitivity (DMIS) by Bennett (2004) and Hammer et al. (2003), language learning strategies by R. L. Oxford (1990), and language learning motivation by Pranawengtias (2022). Through online interviews, this study examined the transcriptions of two English literature students. The results revealed that of the types of language learning strategies undergone by female students, male students did not encounter affective strategies. In addition, the same thing happened with the types of motivation, where only female students encountered intrinsic and extrinsic factors. However, male students only encountered intrinsic factors. Interestingly, this study also underlines how language learning strategies and motivation are inextricably linked in shaping students' intercultural awareness. Overall, this study has shed light on EFL teaching where intercultural awareness can be promoted by accelerating students' language learning strategies (LLSs) and motivations (LLMs) and enabling them to establish a basic visualization of how the target language (foreign language) we learn in the classroom has a profound link with the culture of the target language itself. Thus, spotlighting the idea that learning a foreign language will steer the flow of in-class teaching into cultural learning also becomes the point from the current research.